ANALISIS KEBERADAAN BAKTERI DAN HIGIENE SANITASI PERALATAN MAKAN DI RUMAH MAKAN WILAYAH KERJA PUSKESMAS SIMPANG TIGA PEKANBARU - Betty Nia Rulen; Iin Intarsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The poor of hygiene equipment has an important role in the growth and spread of disease germs and poisoning. Based on data from the Pekanbaru city health office that had supervised food management places (TPM), restaurants that meet health requirements reached 40% in 2018. This study aimed to analyze the bacteria existence and hygiene sanitation of tableware in the restaurant in the working area of Puskesmas Simpang Tiga, Pekanbaru. This descriptive research used an observational method and laboratory tests on the bacteria existence and hygiene sanitation of tableware. The results of this study indicated the presence of bacteria in the washing water of 10 restaurants, for total Coliform as much 80%; and as much as 70% for content of Escherichia coli, the restaurant not eligible of health requirements according to the regulation of the Health Minister of the Republic of Indonesia Number 32 of 2017. Meanwhile, the test results of the bacteria content on the rag showed that for the 100% germ rate, the restaurants were not eligible the health requirements; and for the content of 70% Escherichia coli, the restaurants were also not meet the health requirements according to the Regulation of the Health Minister of the Republic of Indonesia 1096/Menkes/SK/VI/2011. The observation results showed for washing techniques, drying techniques, and storage techniques, all restaurants do not reach the health requirements. This research suggests Simpang Tiga Public Health Center be able to provide counseling of hygiene sanitation and conduct Escherichia coli checks on tableware and supervise food management places properly and continuously in restaurants in their working area.